2019
DOI: 10.3390/su11236590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilization in Selected Phytometric Features and Contents of Bioactive Compounds in Dry Matter of Two Varieties of Basil (Ocimum basilicum L.)

Abstract: This study investigated the effects of sustainable, organic and standard mineral fertilization in selected phytometric features and contents of bioactive compounds in dry matter of two varieties of Ocimum basilicum L. The herbal material was first examined for its phytometric characterisation and then subjected to the combined convective pre-drying and vacuum-microwave finish drying method (CPD-VMFD). The energy consumption for the drying process of plant material in the case of CPD-VMFD is lower in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
3
26
0
Order By: Relevance
“…The increase in the percentage of this ingredient recorded in the studies for this herb when fertilized organically as opposed to minerally ranged between 8.4% for the Aureum variety and 19.3% for the Hot & Spicy variety (Table 4). A similar relationship between the fertilizer used and the content of the main compounds of the headspace fraction was noted by Matłok et al [16] in the herb of the common basil Ocimum basilicum L. In their study, the authors concluded that organic fertilization had an impact on the growth of the main components of the volatile fraction of the dried mass of two varieties of common basil. The organic fertilization involved a peat substrate that was fortified with common nettle extract (10% in terms of weight) and horse manure (20% in terms of weight), followed by soil-applied fertilization with Biolisa N 12,5.…”
Section: Chemical Composition Of Hs-spmesupporting
confidence: 78%
See 2 more Smart Citations
“…The increase in the percentage of this ingredient recorded in the studies for this herb when fertilized organically as opposed to minerally ranged between 8.4% for the Aureum variety and 19.3% for the Hot & Spicy variety (Table 4). A similar relationship between the fertilizer used and the content of the main compounds of the headspace fraction was noted by Matłok et al [16] in the herb of the common basil Ocimum basilicum L. In their study, the authors concluded that organic fertilization had an impact on the growth of the main components of the volatile fraction of the dried mass of two varieties of common basil. The organic fertilization involved a peat substrate that was fortified with common nettle extract (10% in terms of weight) and horse manure (20% in terms of weight), followed by soil-applied fertilization with Biolisa N 12,5.…”
Section: Chemical Composition Of Hs-spmesupporting
confidence: 78%
“…Method of drying (S1), drying kinetics determination (S2), HS-SPME GC-MS herbs analysis (S3), total polyphenolic content (S4), antioxidant activities (S5), color analysis (S6) and statistical analysis (S7) methodology are attached as Supplementary Materials [16,18,19].…”
Section: Plant Materials Preparation and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this, the species that have been investigated for their spontaneous emission were too negligible compared to the high number of plants present in nature. The spontaneous emission of Ocimum basilicum (Ob) was already widely studied [75][76][77][78][79], but only a few papers investigated its varieties and none of these works reported the varieties studied herein. In 2008, Klimánková et al, [80] evaluated five cultivars of basil green cultivar I (Prava zelena), green cultivar II (Trpaslici), red cultivar III (Cinamonette), red cultivar IV (Purple Opaal), and red cultivar V (Rot), and their volatile composition was characterized by linalool, methyl chavicol, eugenol, bergamotene, and methyl cinnamate.…”
Section: Spountaneous Emissionsmentioning
confidence: 99%
“…In 2008, Klimánková et al, [80] evaluated five cultivars of basil green cultivar I (Prava zelena), green cultivar II (Trpaslici), red cultivar III (Cinamonette), red cultivar IV (Purple Opaal), and red cultivar V (Rot), and their volatile composition was characterized by linalool, methyl chavicol, eugenol, bergamotene, and methyl cinnamate. A more recent study reported the SPME components of two basil varieties (Violetto and Genovese) where linalool (18.94% and 22.57% respectively), eugenol (3.95% and 15.02%, respectively) and methyl eugenol (39.17% and 19.39%, respectively) were identified as the main constituents [77]. On the contrary, the whole spontaneous emission of Malaysian O. basilicum flower was represented by estragole (88.18%) [78].…”
Section: Spountaneous Emissionsmentioning
confidence: 99%